Anti-Inflammatory, Anti-Oxidative and Anti-Apoptotic Effects of Thymol and 24-Epibrassinolide in Zebrafish Larvae - Germano A. B. Lanzarin; Luís M. Félix; Sandra M. Monteiro; Jorge M. Ferreira; Paula A. Oliveira; Carlos Venâncio (MDPI AG, 2023)
Thymol (THY) and 24-epibrassinolide (24-EPI) are two examples of plant-based products with promising therapeutic effects. In this study, we investigated the anti-inflammatory, antioxidant and anti-apoptotic effects of the THY and 24-EPI. We used zebrafish (Danio rerio) larvae transgenic line (Tg(mpxGFP)i114) to evaluate the recruitment of neutrophils as an inflammatory marker to the site of injury after tail fin amputation. In another experiment, wild-type AB larvae were exposed to a well known pro-inflammatory substance, copper (CuSO4), and then exposed for 4 h to THY, 24-EPI or diclofenac (DIC), a known anti-inflammatory drug. In this model, the antioxidant (levels of reactive oxygen species-ROS) and anti-apoptotic (cell death) effects were evaluated in vivo, as well as biochemical parameters such as the activity of antioxidant enzymes (superoxide dismutase, catalase and glutathione peroxidase), the biotransformation activity of glutathione-S-transferase, the levels of glutathione reduced and oxidated, lipid peroxidation, acetylcholinesterase activity, lactate dehydrogenase activity, and levels of nitric acid (NO). Both compounds decreased the recruitment of neutrophils in Tg(mpxGFP)i114, as well as showed in vivo antioxidant effects by reducing ROS production and anti-apoptotic effects in addition to a decrease in NO compared to CuSO4. The observed data substantiate the potential of the natural compounds THY and 24-EPI as anti-inflammatory and antioxidant agents in this species. These results support the need for further research to understand the molecular pathways involved, particularly their effect on NO.